On Track to Climate Resilience? Insights from Japanese Railways - Ochsner, Michelle ; 0009-0005-4035-5038; Greenham, Sarah; del Barrio Álvarez, Daniel; Kato, Hironori (Conference on Advanced Systems in Public Transport and TransitData 2025, Kyoto, Japan, 2025-07-01 - 2025-07-04, 2025)
Japan has a long history of managing natural hazards due to its geography and geology. Simultaneously, it is known as a country with a railway system that is highly punctual, reliable, and safe. This research uses an exploratory approach to review climate change adaptation and disaster risk reduction practices in the Greater Tokyo Area. Unstructured interviews with various stakeholders and a literature review discuss how the climate is changing in Japan, what strategies are used amongst railway organisations to manage meteorological hazards, and how railway organisation acknowledge climate change adaptation alongside disaster risk reduction. Results indicate that disaster risk reduction practices still dominate within the railway sector however, more efforts of climate change adaptation set forth by the government may shift practices.